NON-PARAMETRIC METHODS FOR ANALYZING STABILITY OF ABILITY OF CHICKPEA ( CHICKPEA (Cicer arietinum L.) GENOTYPES L.) GENOTYPES - T. LAKSHMI PATHY, A. TRIVIKRAMA REDDY; AND JAYARAME GOWDA, A.VIJAYABHARATHI (The Bioscan, 2018)
A study was conducted to identify chickpea genotypes with stable performance in multi-locations through nonparametric stability parameters. Twenty chickpea genotypes along with three checks were evaluated for pod yield in three locations. Non-parametric stability statistics discriminated the chickpea genotypes based on their pod yield and stability into four sections visually on graphs. The Kang’s rank sum (rs) method identified the genotypes ICC-19830, GNG-1958, PBC-1103, IPC-02-248, JG-11, RKG-155, GCP-105 as high yielding and stable. The genotypes GNG-1958 and PBC-1103 being more stable but the genotype PBC-1103 most preferred one with high Fox TOP statistic value. According to Huehn’s S1, S2, S3 and S6 statistics, the genotypes PBC-1103 and IPC02-248 were the highly stable and high yielding genotypes. The genotypes IPC-02-248, PG-06102 and JG-11 were high yielding and stable as they lie in section 1 of the graph. Majority of parameters identified the genotypes IPC-02-248 and RKG-155 as high yielding and stable. Spearman’s rank correlation among non-parametric statistics showed high degree of positive association of mean yield with Thennarasu’s N2, N3 and N4 and Ketata’s sdy statistics. Genotypes with specific adaptation should be selected based on their ranks in individual environments.